A novel low-crosstalk driveline based on spoof surface plasmon polaritons - Zhao, Shumin (2019)
The crosstalk suppression of multichannel coupled drivelines is studied for high-performance integration of micro-electro-mechanical system arrays. By using traditional drivelines, for example, microstrip lines, the distance between adjacent drivelines should be large enough to reduce the multichannel coupling effects. As a result, the size and the area of ultra-low crosstalk and closed-packaged driveline become an issue for design. To address it, we proposed a new scheme of multichannel spoof surface plasmon polaritons (SSPP)-based drivelines. The new drivelines consist of multiple parallel planar corrugated metallic strips. Thanks to the strong field confinement and localization characteristics of the SSPPs, the coupling effects between drivelines in different channels can be significantly suppressed with no need of any other coupling suppression circuits. For demonstration and investigation, both simulation and measurement are carried out up to 20 GHz. The results show that the crosstalk by using the proposed new drivelines can be reduced by about 10 dB on average. Therefore, the SSPP-based multichannel drivelines would be a good candidate for large-scale advanced integrated devices and systems with requirements of both miniaturization and coupling suppression.